ANALISIS PENGARUH VARIASI PAHAT DAN RADIUS PADA MATERIAL ST 32 TERHADAP HASIL KEKASARAN PERMUKAAN BUBUT RATA MENGGUNAKAN MESIN CNC XTRA 420 - Cohyo Purnomo; Fajar Satriya Hadi; Retno Eka Pramitasari; Mohammad Munib Rosadi (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to determine the effect of tool variation and radius on ST 32 material on the surface roughness outcomes of turning on a CNC XTRA 420 machine. The results can be summarized as follows: the best tool variation in terms of roughness was the DNMG tool with a roughness value of 1.46 µm, radius variation of 0.4 with a roughness value of 1.62 µm. The research uses an experimental method which can be interpreted as the most complete quantitative research approach, in the sense that it fulfills all the requirements for testing cause and effect relationships. Data analysis from the effect of tool variation with radii of 0.4, 0.6, and 0.8 on surface roughness outcomes was conducted using the Mann-Whitney test, which yielded a significance value of 0.050.